A Comparative Study for Good Corporate Governance During Covid-19 Pandemic in Basic Material Industry: A study case in Public Listed Company in Indonesia - Andersen, Matthew; Valentina, Lilia; Laturette, Kazia; Hartono, Wendra (Journal of International Conference Proceedings, 2023)
This aim of this study is to find out the differences the characteristic for Corporate Governance before and during the Covid-19 pandemic. Covid-19 pandemic has devastated global economic condition. Many industries has been affected and faced severe condition to survive. Top level management such as Board of Directors must deal with difficulties situation and uncertainties market condition. Lock down policy has changed habbitual for humans to stay and work from home. The needs for basic materials were increasing during the Covid-19 pandemic. Because of scarcity occured in the market to keep some basic materials, it cause increasing the price of basic materials. Some business has increased the income, including basic materials. Therefore the financial report for basic materials industry have shown positive for income statement, and lead to shareholders to ask the dividend in the Annual general meeting for shareholders. This study is a part of quantitative research and use secondary data. The sample in study this is coming from Basic Materials Industry from public listed companies in the Indonesia Stock Exchange for 2018 – 2020, as 43 companies. This study will use statistic-test which is a difference test or t-test. Independent variables used in this study are Commissioner Independent , Board of Directors, Board of Commissioners, and Audit Committee. This findings will be useful for academician to get some insight or references to help further research.